Challenges of Javanese Language Inheritance in Family: A Cultural and Educational Perspective - Wahyuni, Mita (Centre for Literary and Cultural Studies, 2024)
Javanese is one of Indonesia's most significant regional languages, rich in philosophical values, traditions, and local wisdom. As one of the main tools of cultural communication, this language functions as a medium of conversation and as a carrier of identity and expression of social values of Javanese society. However, in recent decades, the inheritance of Javanese has faced various significant challenges. This inheritance, which should start from the family—as the primary social unit—is now hampered by various factors, such as changes in lifestyle, globalization, and less supportive education policies. This essay aims to analyze the challenges of the inheritance of Javanese in three main dimensions: the dominance of Indonesian and globalization, minimal exposure to Javanese in families, and the limitations of Javanese language learning in formal institutions.